Revitalizing canal irrigation: towards improving cost recovery - Malik, Ravinder Paul Singh; Prathapar, Sanmugam A.; Marwah, Madhavi (International Water Management Institute, 2014)
Cost recovery from irrigation in almost all the countries presents a dismal picture. Low cost recovery coupled with declining government finances has led to the deterioration of both the quality of the built infrastructure and institutions managing and governing such infrastructure. This has created a vicious circle of low cost recovery, poor maintenance of infrastructure, inadequate and unreliable water supply, inefficient and corrupt institutions, and unwillingness of the farmers to pay. Breaking this vicious circle primarily requires identifying ways to improve availability of financial resources. Improving cost recovery from all users, including irrigators of the water, offers one of the most important avenues for raising financial resources. The present study examines some of the important issues that impinge on improving the cost recovery in canal irrigation, and assesses the feasibility of some of the efforts being made to improve cost recovery in irrigation to revitalize canal irrigation.